Towards Clayton Crocket, Deleuze Beyond Badiou: Ontology, Multiplicity, and Event - Šišovski, Jordan (Identities: Journal for Politics, Gender and Culture, 2013)
Author(s): Jordan Šišovski Title (English): Towards Clayton Crocket, Deleuze Beyond Badiou: Ontology, Multiplicity, and Event Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 138 Page Count: 1 Citation (English): Jordan Šišovski, “Towards Clayton Crocket, Deleuze Beyond Badiou: Ontology, Multiplicity, and Event,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 138.